Case report: Ultrasound-Assisted endovascular therapy for carotid artery floating thrombus - Wang, Peng; Wang, Zhenzhen; Pan, Jie; Lu, Kefeng; Sun, Litao; Geng, Yu (Frontiers in Cardiovascular Medicine, 2022)
Background Carotid free-floating thrombus (CFFT) is a rare but sometimes emergent condition. There has been controversy over the optimal treatment strategy. Emerging evidence suggests that endovascular thrombectomy (EVT) may be an alternative to surgery. Accurate alignment of the aspiration catheter and thrombus during EVT is critical but has, so far, remained unresolved. Case summary This is a rare case of CFFT presenting with acute right-sided facial droop and moderate dysarthria in a 77-year-old man. He was in sinus rhythm with a blood pressure of 110/82 mmHg. Both non-contrast CT (NCCT) and head CT angiography (CTA) were unremarkable, while whole-brain CT perfusion (WB-CTP) suggested left hemisphere core infarction. Delayed imaging of the left internal carotid system by 4D-CTA suggested severe proximal obstructive disease, as confirmed by carotid CTA and ultrasonography. The initial two aspirations under DSA were invalid due to the challenging anatomical angle between the thrombus and the catheter. The success of CFFT removal was achieved with a pressure-assisted ultrasound-guided approach that helps to compress the catheter tip toward the thrombus. Conclusion We innovatively report a successful ultrasound-guided EVT for CFFT. Ultrasound assistance can provide quick and effective guidance and may guide tailored aspirations during EVT.